Cannabidiol Does Not Cause Significant Changes to Working Memory Performance in the N-Back Task - Éamon Jones; Styliani Vlachou (MDPI AG, 2021)
Cannabis use can be traced back to several centuries before the Common Era, when it was used for industrial, medicinal and recreational purposes. More recently, over 100 different cannabinoid compounds have been identified, one of which is cannabidiol (CBD), a compound widely used for anti-inflammatory and anxiolytic treatment. The literature surrounding the cognitive effects of CBD is limited, with most studies focusing on the effects of other cannabinoids on cognition. To expand this literature, this study investigated whether CBD causes significant differences to working memory (WM) functioning, as measured by the N-back task. It was hypothesised that CBD does not cause statistically significant differences to WM. In all, 54 participants, 33 females and 21 males, were recruited, with a mean age of 32.63 years. Of these 54 participants, 26 reported using CBD and no other cannabinoids, while 28 reported not using any cannabinoid. The participants were instructed to answer a short online survey to gather basic demographic data and to complete an online N-back task to measure WM. For the computerised N-back task, the participants completed a practice and three test blocks, where they were instructed to respond to whether a series of letter stimuli were presented one trial back (1-back), two trials back (2-back) or three trials back (3-back). Multivariate analysis of covariance yielded no statistically significant difference on either response time or response accuracy data between groups after controlling for how long the participants use CBD and for what reason they use CBD. These results support our hypothesis that CBD does not cause significant changes to WM functioning. Further research is greatly needed to investigate the long-term effects of CBD use on WM and on general cognitive functioning.